Exploring the role of protein palmitoylation in cancer progression and therapy: a comprehensive bibliometric study (2004–2024) - Yu Chen; Yuxuan Dai; Xing Wang; Jian Liu (Discover Oncology)
Abstract Objective This study aims to qualitatively and quantitatively assess the research landscape of palmitoylation in oncology using bibliometric analysis, thereby providing insights into research hotspots and emerging trends. Methods The data were sourced from the Web of Science Core Collection, retrieved using predefined search terms, and comprise review articles and original research papers published in English from 2004 to 2024. Bibliometric analysis and data visualization were performed using VOSviewer, CiteSpace, and Microsoft Excel. Results The United States and China are the leading contributors to research in this field, with Shanghai Jiao Tong University being the most prolific institution in terms of publication output. Current research hotspots in protein palmitoylation related to oncology primarily encompass the enzymatic mechanisms and dynamic regulation of palmitoylation, palmitoylation-mediated lipid metabolic reprogramming and tumorigenesis, palmitoylation-mediated tumor signaling pathways, and targeted cancer therapy strategies based on palmitoylation modification. Current research trends primarily focus on the modulation of critical enzymes and signaling pathways, which influence tumor biology and prognosis. Additionally, emphasis is placed on metabolic reprogramming mediated by protein palmitoylation within the tumor microenvironment, especially regarding its role in tumor responsiveness to chemotherapy and immunotherapy. Conclusion This study provides a comprehensive overview of recent advancements in research regarding protein palmitoylation modifications within oncology.